The aircraft spin - a mathematical approach and comparison to flight test - Bennett, Christopher J.; Lawson, Nicholas J.; Gautrey, Jim; Cooke, Alastair (AIAA, 2017)
A Scottish Aviation Bulldog light aircraft operated by the National Flying Laboratory Centre (NFLC) at Cran eld University, modi ed with research equipment including bre optic sensors for wing strain and fuselage pressure measurements, is used to investigate the dynamics of a fully developed spin. A theoretical model is developed to compare with existing ight test data. In particular, the frequency of the aircraft spin is analysed as a function of the mass distribution of the aircraft to determine the e ect of the fuel load. It is found that the spin frequency is minimally a ected by the fuel load since the moments of inertia corresponding to the engine, for example, are far more signi cant. However, it is con rmed that the yawing e ect of the propeller causes the aircraft to spin faster to the right than to the left.